1968
DOI: 10.1002/polc.5070230123
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of concentrated polystyrene solutions in good and in poor solvents

Abstract: By means of capillary and rotational viscometers flow curves of concentrated polystyrene solutions were obtained. The measurements were carried out at concentrations of 0.184–0.573 volume fraction of polymer, shear stresses of 3 × 101−3 × 106 dyne/cm.2, shear rates of 1 × 10−6 to 1 × 106 sec.−1, and temperatures of 15–120°C. It was shown that both the deterioration of quality of solvent and the decrease of temperature increase the initial Newtonian viscosity and facilitates attainment of the upper Newtonian vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1970
1970
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…From qo(c;T) measurements, Debye et al 1221 found that plots of d !2n VJdT vs. c exhibited pronounced maxima in the moderate concentration range as T approached the theta temperature. Anomalous qo(c; S ) data, similar to those reported here, were observed as early as 1945 by Janssen and Caldwell [23] and more recently by Tager et al [24]. The latter workers also demonstrated the marked differences in non-Newtonian character observed for good-solvent and poor-solvent systems.…”
Section: Discussionsupporting
confidence: 88%
“…From qo(c;T) measurements, Debye et al 1221 found that plots of d !2n VJdT vs. c exhibited pronounced maxima in the moderate concentration range as T approached the theta temperature. Anomalous qo(c; S ) data, similar to those reported here, were observed as early as 1945 by Janssen and Caldwell [23] and more recently by Tager et al [24]. The latter workers also demonstrated the marked differences in non-Newtonian character observed for good-solvent and poor-solvent systems.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, this linear dependence of E η on concentration differs from the corresponding relationships that are typically found for the solutions of linear and/or randomly branched chain polymers, where a break in E η vs c slope is normally observed . Since the appearance of this break may be associated with establishment of entanglement couplings, the observed linearity of E η vs c in dendrimer solutions seems to represent yet another manifestation of dendrimer impenetrability to other dendrimers or their parts.…”
Section: Resultsmentioning
confidence: 98%
“…This model was first proposed by Kargin et al") for the conformation of bulk polymers, and applied to concentrated solutions by Tuger et a1. 20).…”
Section: Introductionmentioning
confidence: 99%